Regulation and the Management of Expectations—Rating Agencies Revisited. (September 2015) - Hinterleitner, Markus; Rosser, Christian
Abstract : In the aftermath of the 2008 crisis, scholars have begun to revise their conceptions of how market participants interact. While the traditional "rationalist optic" posits market participants who are able to process decision‐relevant information and thereby transform uncertainty into quantifiable risks, the increasingly popular "sociological optic" stresses the role of uncertainty in expectation formation and social conventions for creating confidence in markets. Applications of the sociological optic to concrete regulatory problems are still limited. By subjecting both optics to the same regulatory problem—the role of credit rating agencies (CRAs) and their ratings in capital markets—this paper provides insights into whether the sociological optic offers advice to tackle concrete regulatory problems and discusses the potential of the sociological optic in complementing the rationalist optic. The empirical application suggests that the sociological optic is not only able to improve our understanding of the role of CRAs and their ratings, but also to provide solutions complementary to those posited by the rationalist optic.